STUDI KOMPETENSI PROFESIONAL GURU MATA DIKLAT PROGRAM KEAHLIAN ADMINISTRASI PERKANTORAN RUMPUN BISNIS DAN MANAJEMEN PADA SMK DI PRINGSEWU - Astuti, Sariyah; Puspita, Dian; Rahsel, Yoeyong (Lentera: Jurnal Ilmiah Kependidikan, 2018)
The scope of the study in this study is about the level of mastery of the competence of teachers in the eye teacher training productive Office Administration Expertise Program At SMK In Pringsewu District. The core of the study focuses on mastery of learning material mastering indicators, research capability indicators, indicators of research capability and the preparation of scientific papers, and indicators of understanding of insights and educational foundations. The research method used is descriptive method with technique of collecting data of questionnaire scale five category Likert. Data analysis technique used is the calculation of the average score. Based on the calculation results obtained as follows: on indicator of mastery of learning material is in the high category of 4.04. on indicator of research ability is in medium category equal to 3.03. on indicator of research ability and preparation of scientific works, is in the medium category of 3.06., on the indicators of understanding of insight and educational foundation, is in the high category of 4.49. The results show that all dimensions are in the medium and high category, but have not reached the very high category so it is necessary to improve the dimensions.